Seasonal expression of apospory in bahiagrass - Rios, Esteban Fernando (2013)
This paper was presented at the 22nd International Grassland Congress, Sydney, Australia, 15−19 September 2013. Its publication in Tropical Grasslands – Forrajes Tropicales is the result of a co-publication agreement with the IGC 2013 Organizing Committee. Except for adjustments to the journal’s style and format, the text is essentially the same as that published in: Michalk LD; Millar GD; Badgery WB; Broadfoot KM, eds. 2013. Revitalising Grasslands to Sustain our Communities. Proceedings of the 22nd International Grassland Congress, Sydney, Australia, 2013. New South Wales Department of Primary Industries, Orange, NSW, Australia. p. 258–259.